Dynamics of biomechanical indicators for 800-meter running technique in terms of competition for high-class athletes - Rafalovich A.B. ,; Drozdov A.L. ,; Atkishkina T.D. ,; Podtochilin A.M. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to inquire the changes in biomechanical indicators of 800 m running technique in terms of competition for high-class athletes. Methods and structure of the study. The analysis of changes in biomechanical indicators of 800 m running technique of highly qualified athletes at competitions were carried out. Based on high-speed video (250 fps) on straight sections of the track at four points of the distance, the characteristics of running technique (duration of phases, length and speed of running steps) of 19 participants were evaluated. Results and conclusions. Reliably significant (p<0,05) changes from start to finish were revealed: a) increase in the duration of the push-off and support phases, b) decrease in the flight phase. The length and speed of the double step significantly (p<0,05) decrease from the middle of the distance to the finish. At the hypothesis level, it was noted that the decrease in the flight phase is largely associated with increasing fatigue, rather than with a change in running speed. A tendency towards increasing asymmetry of the running step along the distance was revealed.